Trust as an element of informal coordination and its relationship with organizational performance - Marco Tulio F. Zanini; Carmen P. Migueles (EconomiA, 2013)
The main objective of this article is to contribute to a better understanding of trust issues within organizations to expand and refine theoretical constructs. Trust is approached in the economic perspective as a social mechanism for management. We seek to understand the role of trust in the informal coordination of relational contracts. We approach trust as a critical element in the execution of diverse organizational tasks and its mediating relationship with organizational performance. We conclude that trust is central to a better understanding of relational contracts and that investments made in a management style based on trust should observe economic rationality. – – O principal objetivo deste artigo é contribuir para uma melhor compreens\~ao sobre as quest\~oes relativas à confiança dentro das organizaç\~oes, de forma a expandir e refinar construtos teóricos. Confiança é abordada numa perspectiva econômica como um mecanismo social de gest\~ao. Buscamos compreender o papel da confiança na coordenaç\~ao informal dos contratos relacionais. Abordamos a confiança como um elemento essencial para a execuç\~ao de diversas tarefas organizacionais e estudamos a sua relaç\~ao mediadora com o desempenho organizacional. Finalmente, concluímos que a confiança é um elemento central para a melhor compreens\~ao dos contratos relacionais, e que investimentos em um estilo de gest\~ao baseado em confiança devem ter em atenç\~ao à racionalidade econômica.
Keywords: M; M5; M55; J4; J41; 330; Trust; Informal coordination; Relational contract; Organizational performance